al-Zira'ah fi al-Qur'an al-karim : dirasah tatbiqiyah fi 'ahd al-khalifah 'Umar ibn 'Abd al-'Aziz = Agriculture according to al-Quran al-karim : a study on its implementation during the reign of caliphs Omar Abdul Aziz / Omar Mohamed A. Nasr - Nasr, Omar Mohamed A. (2011)
This research entitled The Agriculture According to al-Quran al-karim : A Study on Its Implementation du ring the Reign of Caliphs Umar Abd al-Aziz. The problem statement of this research covers what Allah said for Agriculture as necessary for human life. It is considered as source of food, medicine and garments, which has an important role for the environmental balance and it is the key for developments, which give rise to civilization. The research consists of two chapters and each chapter being divided into three classes and each class contains two subjects. The first chapter covers the importance of agriculture in the environment and human life, definition of agriculture, and the relationship between agriculture and environment, and the agriculture in Holy Quran, the related chapters of the Holy Quran to agriculture sector, the legal plants and animals, and illegal animals in the Holy Quran, illustrations of agriculture in the Quran as well as comparison of plants or agriculture and animal products. The third chapter covers, the memoirs of Umar Bin-Abd-al-aziz, including his name, family, life, succession and what he afforded for agriculture to achieve satisfaction in nations of Islam by following the Quran and Sunnah with the clarifications of possibility and the resources of animals and plants in this time by rising the nations and impediment of Islamic nations in this way as well as utilizing from the previous experiments. In conclusion, agriculture has a high value in the Holy Quran. Agriculture is an important for human life, where, no life in the world without agriculture. The most important solution for the Islamic world to rise up by following the Holy Quran with its value of information. This is much enough to achieve developments and conduct the correct way. Recommendation of this study: food security and the personal satisfaction are important term for the honor of Islamic nation and its union. Therefore, we must follow the Quran chapters to maintain the balance and combat decaying, saving funds in Islamic countries as well as we must attempt to conduct the right way and impose the mistakes. Indeed, there is no poorness but there are wrong distributions. The period of Umar Bin Abd al-Aziz was marked by the fair, wisdom, obeying, understanding, and good politically. He gave confidence to these nation to return back to its clear past.